Growth, Forage Quality, and Economics of Cover Crop Mixes for Grazing - J. K. Farney; G. F. Sassenrath; C. Davis; DeAnn Presley (Kansas Agricultural Experiment Station Research Reports, 2018)
Cover crops offer many potential benefits to crop production. They diversify the plant system, increase soil organic matter, and reduce erosion. However, they can be expensive to plant. By grazing the cover crops, farmers can recover some of the expenses associated with growing cover crops. Grazing also increases the nutrients to the field, further enhancing the productive capacity of the soil. Many cover crop mixtures are currently available on the market. However, it is not clear how useful the multi-species cover crops mixtures are, or their potential impact on economics of production. Moreover, many of the cover crop mixes being sold contain species that are potentially harmful to either humans or cattle. For example, some cattle are sensitive to hairy vetch (Farney et al., 2016). Buckwheat, a valuable and frequently used cover crop, causes serious allergic reactions in some human populations, making it especially unsuitable for growing regions that also produce wheat. To avoid cross-contamination of buckwheat with wheat, the U.S. Department of Agriculture Natural Resources Conservation Service (NRCS) requires an exclusion of buckwheat by 30 feet and two years from any commercial wheat production fields. NRCS has restricted the use of buckwheat in cover crop mixes for regions that grow wheat (NRCS, 2016). Many plants are good for planting as cover crops. There are three general categories of plants that are commonly used as cover crops, each with a unique growth habit and rooting structure. In this study, we chose common plants from each of these major groups: grasses, brassicas, and legumes. The soils in southeast Kansas were developed under the tallgrass prairie. Grasses have a dense, fibrous rooting system that is ideally suited for growth in the claypan soils of this region. Studies of soil microbial activity indicate that grasses may enhance microbial activity at lower soil layers, better using more of the soil profile for extracting nutrients and water (Hsiao et al., 2018). The grasses chosen for this study included winter barley, winter oats, cereal rye, and winter wheat. Brassicas have a taproot that creates large holes in the soil called macropores. These macropores break up the soil structure. As the large taproot decays, it supports microbial activity and further improves the soil structure. Brassicas also release unique compounds into the soil, such as glucosinolates, that have been shown to suppress disease organisms in the soil such as fungi and nematodes. The brassicas used in this study included tillage radish and purple-top turnip. Legumes improve the soil by increasing the soil nitrogen. Most legumes have a fibrous rooting system. The legumes used in this study included berseem clover and Austrian winter pea.
Keywords: Cover crop mixes; grazing; forage quality; economics of cover crops